PENERAPAN MODEL PBL BERBASIS PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV - Robby Hermawan; Delawanti Chrisyarani, Denna; Tumijan; Sukowati, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education learning in elementary schools needs to create an active, meaningful, and contextual learning environment to enable students to understand and apply Pancasila values in their daily lives. However, the learning process in Grade IV at SDN Pisangcandi 2 Kota Malang was still predominantly teacher-centered, resulting in limited student participation and less optimal learning outcomes. Pre-cycle data indicated that the learning mastery rate was only 40%, with an average score of 71.6. This study aimed to describe the implementation of a Problem-Based Learning (PBL) model integrated with a deep learning approach and to examine the improvement of students’ learning outcomes on the topic of Gotong Royong (mutual cooperation).This study employed Classroom Action Research using the Kemmis and McTaggart model conducted in two cycles, involving 28 fourth-grade students as the research subjects. Data collection techniques included tests, observations, and documentation. The findings revealed that the implementation of PBL integrated with a deep learning approach gradually improved students’ learning outcomes. Classical learning mastery increased from 40% in the pre-cycle stage to 46% in Cycle I Meeting 1, 64% in Cycle I Meeting 2, and 90% in Cycle II, while the average score improved to 84.2. Therefore, the deep learning-based PBL model was proven effective in improving students’ learning outcomes in Pancasila Education.